Design and test of a setup for calorimetric measurements of AC transport losses in HTS racetrack coils. (3rd March 2023) - Vargas-Llanos, Carlos Roberto; Krämer, Joachim; Noe, Mathias; Grilli, Francesco
Abstract: The estimation and measurement of AC losses in coils based on high-temperature superconductors (HTS) are relevant aspects of HTS applications. They influence the cooling power requirement, operating temperature and efficiency, which can be decisive in the construction and implementation of superconducting equipment, such as superconducting electrical machines. The measurement of losses due to AC transport current (without external magnetic field) is not an easy task. Several efforts have been made to measure these AC transport losses in superconducting coils with a calorimetric approach by trying to minimize the influence of the environment, improve the accuracy and ensure the reproducibility of the results. This work presents the design and construction of a setup to measure transport AC losses in high-temperature superconducting coils based on a calorimetric approach (boil-off method). The evaporated cryogen (nitrogen) related to the dissipation of energy is collected by using a 3D printed bubble collector that guides the gas into a flow sensor. A box-inside-a-box approach is used to surround the measurement chamber with a cryogenic environment. This approach allows re-directing the heat transfer from the surroundings into an intermediate zone (space between external and internal box). Since this intermediate zone operates under cryogenic temperatures, the noise and the heat transfer in the internal part of the setup are reduced. A statistical analysis of the results based on a standard load cycle, average value, and standard deviation calculations allows assessing the variability in the measurements and expressing the results as average value and uncertainty range. The calibration and reproducibility of the measurements are verified with a set of resistors under different conditions and during different weeks. Finally, the AC transport losses in a racetrack coil for an electrical machine application are measured and compared with 3D simulation results based on the homogenization of the T-A formulation.